(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
The article explores the potential of physical education and sport as effective tools for preventing and counteracting bullying in general secondary education institutions. The authors emphasize that bullying, as a form of school violence, remains a significant threat to children’s physical and psychological well-being. However, physical activity and sport contribute to building healthy lifestyles, enhancing self-esteem, and fostering essential social skills such as cooperation, empathy, and mutual respect, thereby reducing the risk of aggression and social exclusion among youth. A key focus is placed on the concept of "Sport for Development", which integrates physical training with the cultivation of life skills, trust, and teamwork. This concept is promoted as a modern educational strategy for strengthening social cohesion and encouraging pro-social behavior among students. The article draws on international practices, particularly UNICEF initiatives, that support children’s rights to safe play and development through sport. It also addresses the dual nature of sport-while it has the capacity to foster inclusion and reduce social distance, it can also be a space where bullying and violence occur, especially in competitive or highly commercialized environments. The study underscores the need for comprehensive training of physical education teachers to recognize signs of bullying, apply appropriate pedagogical strategies, and create a supportive environment that encourages students to speak up and seek help. The authors call for a revision of traditional authoritarian teaching models in favor of democratic, human-centered approaches. The integration of sport into broader educational goals can enhance not only physical fitness but also resilience, solidarity, and emotional well-being, contributing to the holistic development of students. Ultimately, the article supports the idea that reimagining school-based physical education through the lens of social responsibility and inclusiveness can significantly contribute to bullying prevention and a healthier school culture.